Problematika Pembelajaran Daring di Masa Pandemi Covid-19 dan Solusi Pemecahannya - Asmuni Asmuni (Jurnal Paedagogy, 2020)
The purpose of this study was to analyze the problems of online learning during the Covid-19 pandemic and the solutions to solve them. This type of research is literature study or library research using secondary data sources collected through textbooks, e-books, perodical, statutory regulations, websites, and other sources relevant to the research problem. The research data were analyzed qualitatively with an interactive model, which consists of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the implementation of online learning during the Covid-19 pandemic has various problems experienced by teachers, students, and parents. The teacher's problems are in the form of weak mastery of IT and limited access to supervision of students, from students in the form of inactivity in learning, limited support facilities and internet network access, while from parents in the form of limited time in accompanying their children during online learning. These various problems can be overcome by increasing competency in IT mastery, intensive supervision by involving the role of parents, and providing manual assignments.